Studying Cell-like and Humoral Factors of Immunity and the Definition of Immune Status in Sheltopusik Lizards (Pseudopus apodus) with the Helminthiasis Caused By Entomelas Sp. Nematodes - Zhelankin, R V (KnE Life Sciences, 2018)
Sheltopusik lizards (Pseudopus apodus) are natural carriers of the nematode Entomelas sp., which are capable of striking the majority of lizard species, quite often causing their deaths. In this article, the parameters of the immune status of the sheltopusik lizard with helminthiasis are described, as are the changes when deworming is performed with the medicine “Reptilife-plus” and immunocorrections with the medicine Immunofan.